A Systematic Approach for Semiconductor Half-Heusler - Lim, Wei Yang Samuel; Zhang, Danwei; Duran, Solco Samantha Faye; Tan, Xian Yi; Tan, Chee Kiang Ivan; Xu, Jianwei; Suwardi, Ady (Frontiers in Materials, 2021)
The key to designing a half-Heusler begins from the understanding of atomic interactions within the compound. However, this pool of knowledge in half-Heusler compounds is briefly segregated in many papers for specific explanations. The nature of the chemical bonding has been systematically explored for the large transition-metal branch of the half-Heusler family using density-of-states, charge-density, charge transfer, electron-localization-function, and crystal-orbital-Hamilton-population plots. This review aims to simplify the study of a conventional 18-electron configuration half-Heusler by applying rules proposed by renowned scientists to explain concepts such as Zintl-Klemm, hybridization, and valence electron content (VEC). Atomic and molecular orbital diagrams illustrate the electron orbital transitions and provide clarity to the semiconducting behavior (VEC = 18) of half-Heusler. Eighteen-electron half-Heusler usually exhibits good thermoelectric properties owing to favorable electronic structures such as narrow bandgap (<1.1 eV), thermal stability, and robust mechanical properties. The insights derived from this review can be used to design high-performance half-Heusler thermoelectrics.